2015
DOI: 10.1002/jwmg.1001
|View full text |Cite
|
Sign up to set email alerts
|

Male greater sage‐grouse detectability on leks

Abstract: It is unlikely all male sage‐grouse are detected during lek counts, which could complicate the use of lek counts as an index to population abundance. Understanding factors that influence detection probabilities will allow managers to more accurately estimate the number of males present on leks. We fitted 410 males with global positioning system and very high frequency transmitters, and uniquely identifiable leg‐bands over 4 years in Carbon County, Wyoming. We counted male sage‐grouse using commonly used lek‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 48 publications
5
47
0
Order By: Relevance
“…The second source of uncertainty was addressed by conducting multiple surveys and estimating detectability (i.e., the probability of detecting ≥1 male at an active lek; MacKenzie et al , Blomberg et al ). Although we did not estimate the detectability of individual males on leks, those values are generally high (Fremgen et al ) and, based on our data, similar between helicopter and ground counts. However, non‐detection of males on leks, and possibly disturbance from helicopters, may have led to a small negative bias in our estimates of lek detection probabilities.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The second source of uncertainty was addressed by conducting multiple surveys and estimating detectability (i.e., the probability of detecting ≥1 male at an active lek; MacKenzie et al , Blomberg et al ). Although we did not estimate the detectability of individual males on leks, those values are generally high (Fremgen et al ) and, based on our data, similar between helicopter and ground counts. However, non‐detection of males on leks, and possibly disturbance from helicopters, may have led to a small negative bias in our estimates of lek detection probabilities.…”
Section: Discussionsupporting
confidence: 51%
“…McCaffery et al () used N‐mixture models to estimate per‐occasion detection probability of males over a 13‐year period in Montana, but these models have been discounted by some (Barker et al ) and our estimates of detection probability are for leks rather than males. Other studies have reported detectability of marked males on leks (Johnson and Rowland , Baumgardt , Blomberg et al , Fremgen et al ), mean annual lek attendance (Blomberg et al ), or daily lek attendance rates (Fremgen ) rather than detectability of leks. Additional dual‐frame lek survey studies, especially in larger populations with less fragmented habitat, are needed to determine whether detection probability of leks in the PPR is comparable with other populations.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of support for either visual obstruction or Julian date in our sightability model suggests vegetation is not a significant source of visibility bias in our data. In a similar study in Wyoming, USA, Fremgen et al () concluded that sagebrush height was a significant covariate in their sightability model after removing time and effort covariates. Wyoming big sagebrush and mountain big sagebrush were listed as dominant species in lower and higher elevations, respectively, in their study.…”
Section: Discussionmentioning
confidence: 98%
“…For availability and detection probabilities, we assumed their product was the mean estimate previously reported from sightability models (pnormalapdt = 0.87; Fremgen et al. ). We similarly simulated counts of yearlings )(cyearlingitalicijt, and the observed count used in analyses was: cijt=cadultitalicijt+cyearlingitalicijt.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, detectability of grouse may be influenced by visual obstruction from vegetation, snow, and topography (Fremgen et al. ) as well as visibility changes due to weather and time of day (Baumgardt et al. ).…”
Section: Introductionmentioning
confidence: 99%